Dynamics of Relationship Between Macroeconomic Fundamentals and Exchange Rate: A Comparison of Advanced and Least Developed Countries - Fakher, Amjad; Akbar, Muhammad; Khan, Rana Ejaz Ali (Asian Journal of Economic Modelling, 2021)
The exploration of relationship between macroeconomic fundamentals and exchange rate is needed in the perspective of economic structure of the economies. The focus of current study is to inquire the dynamics of exchange rate behavior in response to macroeconomic fundamentals for advanced and least developed countries. The Pooled Mean Group regression based on panel ARDL and Panel Granger Causality Test are employed on annual panel data sets for the time period 1995-2015. The results evidence a strong relationship between macroeconomic fundamentals and exchange rate volatility in advanced countries and a moderate relationship in least developed countries. The exchange rate level has been observed entirely governed by the selected set of macroeconomic fundamentals in both group of countries. The results validate the fundamental macroeconomic models of exchange rate determination as the macroeconomic fundamental indicators play an important role in the determination of exchange rate volatility as well as exchange rate level. It may be concluded that the relationship between fundamental macroeconomic indicators and exchange rate behavior is sensitive to the economic structure of the countries.